ChemInform Abstract: (3′—5′)‐Cyclic Dinucleotides: Synthetic Strategies and Biological Potential. Issue 48 (26th November 2013) - Clivio, Pascale; Coantic‐Castex, Stephanie; Guillaume, Dominique
Abstract Review: 193 refs.